Atezolizumab plus anthracycline-based chemotherapy in metastatic triple-negative breast cancer: the randomized, double-blind phase 2b ALICE trial - Andreas Hagen Røssevold; Nikolai Kragøe Andresen; Christina Bjerre; Bjørnar Gilje; Erik Jakobsen; Sunil Xavier Raj; Ragnhild Sørum Falk; Hege G. Russnes; Thea Jahr; Randi R. Mathiesen; Jon Lømo; Øystein Garred; et al. (2022)
Immune checkpoint inhibitors have shown efficacy against metastatic triple-negative breast cancer (mTNBC) but only for PD-L1positive disease. The randomized, placebo-controlled ALICE trial (NCT03164993, 24 May 2017) evaluated the addition of atezolizumab (anti-PD-L1) to immune-stimulating chemotherapy in mTNBC. Patients received pegylated liposomal doxorubicin (PLD) and low-dose cyclophosphamide in combination with atezolizumab (atezo-chemo; n = 40) or placebo (placebo-chemo; n = 28). Primary endpoints were descriptive assessment of progression-free survival in the per-protocol population (>3 atezolizumab and >2 PLD doses; n = 59) and safety in the full analysis set (FAS; all patients starting therapy; n = 68). Adverse events leading to drug discontinuation occurred in 18% of patients in the atezo-chemo arm (7/40) and in 7% of patients in the placebo-chemo arm (2/28). Improvement in progression-free survival was indicated in the atezo-chemo arm in the per-protocol population (median 4.3 months versus 3.5 months; hazard ratio (HR) = 0.57; 95% confidence interval (CI) 0.33–0.99; log-rank P = 0.047) and in the FAS (HR = 0.56; 95% CI 0.33–0.95; P = 0.033). A numerical advantage was observed for both the PD-L1positive (n = 27; HR = 0.65; 95% CI 0.27–1.54) and PD-L1negative subgroups (n = 31; HR = 0.57, 95% CI 0.27–1.21). The progression-free proportion after 15 months was 14.7% (5/34; 95% CI 6.4–30.1%) in the atezo-chemo arm versus 0% in the placebo-chemo arm. The addition of atezolizumab to PLD/cyclophosphamide was tolerable with an indication of clinical benefit, and the findings warrant further investigation of PD1/PD-L1 blockers in combination with immunomodulatory chemotherapy.